A Wandering Missionary's Burden: Persistent Fever and Progressive Somnolence in a Returning Traveler. (15th July 2021) - Yagnik, Kruti J; Pezo-Salazar, Alonso; Rosenbaum, David; Jaso, Jesse Manuel; Cavuoti, Dominick; Nelson, Benjamin; Chancey, Rebecca J; McKenna, Megan L; Castellino, Laila M
Abstract: Human African trypanosomiasis incidence has declined, but diagnosis remains difficult, especially in nonendemic areas. Our patient presented with fever, progressive lethargy, and weight loss for 5 months and had previously traveled to Ghana and Cameroon but had not been to areas with recently reported African trypanosomiasis. Extensive workup was negative, except for lymphocytic pleocytosis in cerebrospinal fluid; ultimately, a bone marrow aspiration revealed necrotizing granulomatous inflammation with 2 trypanosomes discovered on the aspirate smear, consistent with Trypanosoma brucei . The patient was treated with combination nifurtimox and eflornithine with full recovery.